2012
DOI: 10.1563/aaid-joi-d-10-00061
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Smoking and Bleeding on Probing

Abstract: The objective of this study was to assess and compare bone loss (BL) around the dental implant platform as well as the presence of bacterial plaque (PBP), bleeding on probing (BOP), and periodontal probing depths (PD) of teeth and dental implants of smokers and nonsmokers. Three hundred forty-seven teeth and 98 implants of 20 randomly selected patients were assessed (12 smokers and 8 nonsmokers). The specimens were divided into 4 groups according to the site probed. Group 1 included smoker implant sites, group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…27 It is suggested that nicotine exerts vasoconstriction on gingival blood vessels, which in turn reduces gingival bleeding in smokers compared with individuals who do not smoke. 28,29 The present results clearly indicate why cigarette smokers and vaping individuals showed fewer percentage sites with BOP as compared with NS.…”
Section: Discussionsupporting
confidence: 61%
“…27 It is suggested that nicotine exerts vasoconstriction on gingival blood vessels, which in turn reduces gingival bleeding in smokers compared with individuals who do not smoke. 28,29 The present results clearly indicate why cigarette smokers and vaping individuals showed fewer percentage sites with BOP as compared with NS.…”
Section: Discussionsupporting
confidence: 61%
“…However, CS remain unaware of the continuous oral tissue inflammatory changes as they present less bleeding signs in gingival tissues compared with NS. This is due to the nicotine that exerts vasoconstriction on gingival blood flow, which in turn reduces gingival bleeding in smokers compared with individuals who do not smoke . Furthermore, recent data suggest that irrespective of the smoking status, increased mean BOP in supportive periodontal therapy patients relates to disease severity and periodontal instability, while smokers demonstrate lower mean BOP concomitantly with an increased prevalence of residual PDs .…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed a significant increase in periimplant marginal bone loss in smokers compared with nonsmokers. 24,31-33 de Souza et al 34 reported that causative mechanism of the connection between smoking and periimplant bone loss was vasoconstriction of the periimplant tissue. In the previous studies, patients were pooled irrespective of their periodontal/periimplant health or oral hygiene status and all types of patients (healthy, with periimplant mucositis, and periimplantitis) were included.…”
Section: Discussionmentioning
confidence: 99%